2004
DOI: 10.1002/jnr.20202
|View full text |Cite
|
Sign up to set email alerts
|

Role of N‐methyl‐D‐aspartate receptors in gastric mucosal blood flow induced by histamine

Abstract: Ionotropic N-methyl-D-aspartate (NMDA) receptor agonists, L-aspartic acid (L-Asp) and NMDA, have been shown to inhibit histamine-stimulated acid secretion, but their effect on gastric mucosal blood flow (GMBF) is largely unknown. The aim of this study was to investigate whether L-Asp and NMDA inhibit histamine-stimulated GMBF and to examine the expression patterns of NMDA receptor subunits NR1, NR2A, and NR2B in rat stomach. Laser Doppler flowmetry was used to measure gastric blood flow in anesthetized rats. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
6
4
0
Order By: Relevance
“…Spontaneous acid secretion from the preparation was 1.232 ± 0.067 μmole/15 min, a value similar to the basal acid secretion in vivo [34] and in vitro [22]. In such preparations, taurine induced acid secretion in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 63%
“…Spontaneous acid secretion from the preparation was 1.232 ± 0.067 μmole/15 min, a value similar to the basal acid secretion in vivo [34] and in vitro [22]. In such preparations, taurine induced acid secretion in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 63%
“…Results from in situ hybridization studies have demonstrated the presence of mRNA for NRl and NMDA [10,11,33] in both myenteric and submucosal ganglia. The distribution pattern of NR1, NR2A and NR2B-containing NMDA receptors in rat stomach is determined immunohistochemically using specific antibodies against NR1, NR2A and NR2B (Figure 3) [34]. These findings are also consistent with the idea that the enteric glutamate receptors are involved in neurogenic motility [15,35] or secretion of the stomach [7,34].…”
Section: Ionotropic Glutamate Receptorssupporting
confidence: 68%
“…The distribution pattern of NR1, NR2A and NR2B-containing NMDA receptors in rat stomach is determined immunohistochemically using specific antibodies against NR1, NR2A and NR2B (Figure 3) [34]. These findings are also consistent with the idea that the enteric glutamate receptors are involved in neurogenic motility [15,35] or secretion of the stomach [7,34]. Recently, the NRl subunits have been localized immunohistochemically in peripheral terminals of primary afferent nerves of dorsal root ganglia [34,36].…”
Section: Ionotropic Glutamate Receptorssupporting
confidence: 63%
See 2 more Smart Citations